Commercial Space Technologies and Applications: Communication, Remote Sensing, GPS, and Meteorological Satellites, Second Edition - Razani, Mohammad; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This new edition introduces and examines the space technologies that are benefiting our everyday life. Space provides a unique environment to carry out scientific research that is otherwise impossible on Earth, including the fields of medicine, pharmaceuticals, metallurgy, physics, engineering, and biology. It also offers a platform from which GPS, Communication, Weather Forecasting, Remote Sensing, and other commercial satellites provide global services; this text highlights the technologies behind these achievements. Each chapter now includes the addition of exercises and problems, and the content covers new satellites and emerging technologies. It explores the ever-improving quality of satellite services and investigates the ways in which to bring about higher resolution satellite imagery and lowered costs of satellite. The focus of this updated book is on man-made satellites, which are becoming smaller, smarter, cheaper, easier to launch, and less susceptible to interference. Furthermore, the book considers the advances made in electronics, semiconductors, modulation, access, and multiplexing techniques affecting the satellite industry.
1. Overview -- 2. Commercial Space Technologies -- 3. Satellites -- 4. Future Space Technologies -- 5. Information, Communication, and Space Technologies
Includes bibliographical references and index.
Also available in print format.
Keywords: Space industrialization; Artificial satellites in telecommunication; Scientific satellites; TECHNOLOGY & ENGINEERING / Microwaves; TECHNOLOGY & ENGINEERING / Telecommunications; Future Space Technologies; Information and Communication Technology; Information and Communication Technology and Space Technology; Satellites; Space Technology; Electronic books